2020
DOI: 10.7717/peerj.8628
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of megafauna on the Bering Sea slope based on ROV survey

Abstract: Video surveys were carried out during the 75th cruise of the RV Akademik M.A. Lavrentyev (June 2016) along the northern slope of the Volcanologists Massif, in the south-western Bering Sea. The seafloor was explored using the ROV Comanche 18. Seven dives were performed in the depth range from 4,278 m to 349 m. Overall, about 180 species of megafauna were recognised. Fifteen types of megafauna communities corresponding to certain depth ranges were distinguished based on the most abundant taxa. Dominance changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
(52 reference statements)
0
17
4
Order By: Relevance
“…Bathymetry. A deep-sea (bathyal) species, so far recorded at 670-761 m depth (for discussion of the different usage of the term "bathyal", see Rybakova et al, 2020).…”
Section: Dendronotus Jamstecimentioning
confidence: 99%
“…Bathymetry. A deep-sea (bathyal) species, so far recorded at 670-761 m depth (for discussion of the different usage of the term "bathyal", see Rybakova et al, 2020).…”
Section: Dendronotus Jamstecimentioning
confidence: 99%
“…It can be explained by possible interspecies interactions. Rybakova et al [44] showed the abyssal community in the Bering Sea being dominated by another elpidiid species, Kolga kamchatica Rogacheva. The latter may occupy the same trophic niche as Peniagone replacing Peniagone species in the Bering Sea.…”
Section: Discussionmentioning
confidence: 99%
“…The species has been reported from eastern Russia at depths of 64-145 m off the island of Paramushir (Naumov 1960;Antsulevich 1987Antsulevich , 2015, from 8-24 m in Avacha Bay on the east coast of the Kamtchatka Peninsula (Schuchert et al 2016), and from Matua Island . Meanwhile, Rybakova et al (2020) reported Candelabrum sp. from video surveys of the northern slope of Volcanologists Massif, southwest Bering Sea, at bathyal and abyssal depths (3450-3610 m; 4277-4278 m).…”
Section: Systematicmentioning
confidence: 99%